2021
DOI: 10.1002/ehf2.13719
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intraventricular haemodynamic forces misalignment on left ventricular remodelling after myocardial infarction

Abstract: Aims Altered left ventricular (LV) haemodynamic forces (HDFs) have been associated with positive and negative remodelling after pathogenic or therapeutic events. We aimed to identify LV HDFs patterns associated with adverse LV remodelling (aLVr) in reperfused segment elevation myocardial infarction (STEMI) patients. Methods and results Forty‐nine acute STEMI patients underwent cardiac magnetic resonance (CMR) at 1 week (baseline) and after 4 months (follow‐up). LV HDFs were computed at baseline from cine CMR l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
2
15
0
1
Order By: Relevance
“…Many studies have demonstrated that multiple factors play a role in this complex adaptative phenomenon by using CMR [ 34 ]. However, it is still unknown if iPPM may facilitate adverse remodeling or the redistribution of intracavitary hemodynamic forces, which appears to be one of the leading mechanisms of remodeling [ 35 ]. Further studies with follow-up imaging and a larger cohort are needed to clarify these relationships and to assess the real prognostic value of iPPM.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that multiple factors play a role in this complex adaptative phenomenon by using CMR [ 34 ]. However, it is still unknown if iPPM may facilitate adverse remodeling or the redistribution of intracavitary hemodynamic forces, which appears to be one of the leading mechanisms of remodeling [ 35 ]. Further studies with follow-up imaging and a larger cohort are needed to clarify these relationships and to assess the real prognostic value of iPPM.…”
Section: Discussionmentioning
confidence: 99%
“…In HFrEF patients HDFs are significantly lower and misaligned, diverging from the normal apex-to-base direction toward the latero-septal one ( 29 ). A recent pathophysiological model suggested a link between HDFs misalignment/re-alignment and adverse-remodeling/reverse-remodeling ( 27 , 28 ). Cardiac endothelial mechano-receptors can distinguish changes in shear stress vectors (tangential vs. perpendicular direction) and activate ultrastructural adaptive responses, such as turnover of contractile proteins and regulation of myofibril orientation ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…HDF analysis can differentiate heart failure patients with preserved ejection fraction compared to controls with similar ejection fraction ( 11 ), reveal subclinical dysfunction due to cardiotoxicity from anthracycline chemotherapy ( 30 ), and it was the first left ventricular parameter to testify the impact of precapillary pulmonary hypertension on cardiac function ( 31 ). As HDF drives the intraventricular pressure gradient exchanged within the myocardium, stimulation of mechanoreceptors may provoke activation of intracellular pathways involved in cardiac adaptation and remodeling ( 32 , 33 ). Identification of subtle kinetic dysfunction is also possible through HDF analysis, leading to detection of mechanical abnormalities in asymptomatic patients ( 11 ).…”
Section: Discussionmentioning
confidence: 99%